Mozambique Agriculture Support Policy Review : Realigning Agriculture Support Policies and Programs - World Bank (Washington, DC, 2022)
This report assesses agriculture policy support estimates in Mozambique. These estimates represent the monetary value assigned to different agriculture support policies and programs using the Organization for Economic Cooperation and Development (OECD) methodology for 2018. The advantages of using the OECD methodology are that: (a) it provides a systematic and integrated view of agriculture support policies and programs (not limited to the more traditional public expenditure reviews or rate of protection); (b) given the large number of countries using this same methodology to measure support estimates, an immediate benchmarking is possible across a large set of comparators; and (c) the methodology is simple and can be integrated into the agriculture public policy analysis conducted by the Government and other stakeholders. This assessment aims to support the Mozambique Government in reviewing its agriculture policies and programs, in particular to: (a) provide new estimates and a new approach to assess sector support for policy decision making; (b) allow for benchmarking agriculture support policies with a large global database of countries using the same estimate methodology; and (c) help kickstart a policy dialogue on realigning agriculture policies and programs in Mozambique towards greater sector competitiveness and fast economic recovery from the Coronavirus disease (COVID-19) pandemic, increased food security and nutrition outcomes, and climate sustainability through a build back better approach.